Mediterranean spotted fever and its complications in Mostaganem, Algeria‎ - S., Bestaoui; NH, Amar; M, Fellah; HF, Bouhalloufa; F.Z., Adli (International Journal of Medicine, 2025)
Mediterranean Spotted Fever (MSF) is an ancient anthropozoonosis of bacterial origin, in which ‎the cause is Rickettsia conorii in which the vector of transmission to humans is the brown dog ‎tick by bite. It is a seasonal disease raging in an endemic state in the Mediterranean region, ‎including our region of Mostaganem (Western Algeria). It was a retrospective study based on ‎the records of hospitalized patients at the infectious diseases department in Mostaganem, ‎recording 36 cases of MSF, from 2023 to 2024. The majority of patients were male and had ‎been in contact with dogs, both domestic and wild. In addition, the majority had a history of ‎diabetes or hypertension and had taken antibiotics before hospitalization. Complications were, ‎therefore, described in 12 of the 36 patients and were mainly nephrological, articular, cardiac, ‎etc. The Direct Current (DC) of our patients was based on Raoult’s diagnostic criteria given the ‎endemic zone, because of the non-availability of serology, or the polymerase chain reaction ‎‎(PCR) test. Although It remains a benign disease, it can be responsible for serious ‎complications, whether reversible or not. It must be systematically evoked in the face of febrile ‎eruptions during hot seasons in countries around the Mediterranean, including ours‎.